Determinants of Local Original Income The Era of Special Autonomy for the Government of Aceh Province - Lestari Sukarniati; Firsty Ramadhona Amalia Lubis (Optimum: Jurnal Ekonomi dan Pembangunan, 2021)
Aceh's special autonomy status allows the province to be able to obtain a larger percentage of financial resources to finance its development. The purpose of this study was to determine the influence of government spending, GRDP, and population in increasing Aceh's local revenue. This study uses a quantitative approach, the analysis tool used is panel data regression which is processed using Stata. The results of the study prove that government expenditure, GRDP, total population have a positive and significant effect on the local revenue of Aceh Province for the period 2011-2018.